EFEKTIVITAS KOMUNIKASI ANTARA PENYULUH DAN KELOMPOK TANI DI KAMPUNG RIMBA JAYA KABUPATEN BIAK NUMFOR - Priskila Estetika Padwa; Agus Sumule; Maria A. P. Palit (Sosio Agri Papua, 2020)
Residents in Rimba Jaya Village generally work as farmers. In Rimba Jaya Village there are 13 farmer groups that have been trained by extension agents to increase agricultural output. From 13 farmer groups, there are 7 groups that have been confirmed from pre-beginner to beginner groups, these groups are considered the most active in Rimba Jaya village and 6 groups that have not been confirmed and are considered not active in participating in extension activities. Based on the problems that arise, the purpose of this study is: Knowing the effectiveness of communication between farmer groups and PPL in channeling agricultural innovation. Knowing the elements of communication that shape the effectiveness of communication that is appropriate for farmer groups Knowing the factors that influence the effectiveness of communication between farmer groups and PPL. The research method used in this study is descriptive method. The sampling method used in this study is to use a random sampling system that is a sampling technique from population members that is carried out randomly and processed by tabulation. Based on the results of this study, it can be concluded that the effectiveness of communication is declared effective with a total score of 603.5. The elements that make up Communication effectiveness are communicators, innovations / information, and communicants (farmer groups). Factors that influence the effectiveness of communication are communicants (formal education, non-formal education, age, farming experience), innovation / information (material, use of language and communicators (media, methods).